PENINGKATAN KUALITAS PEMBELAJARAN MELALUI IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH DI SEKOLAH DASAR - Ivandi Akmal (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to describe the implementation of academic supervision by school principals in an effort to improve the quality of learning in elementary schools. Academic supervision is one of the managerial functions of school principals that focuses on the professional development of teachers in carrying out the learning process. The research method used is descriptive qualitative with a case study approach in one public elementary school. Data were obtained through interviews, observations, and documentation of the principal, teachers, and educational staff. The results of the study indicate that planned, systematic, and continuous academic supervision can improve teachers' competence in designing, implementing, and evaluating the learning process. The impact can be seen in increased student engagement, a more conducive classroom atmosphere, and more optimal learning outcomes. Thus, the implementation of academic supervision by the principal plays a significant role in improving the quality of learning in elementary schools.